THERMOGRAVIMETRIC ANALYSIS OF PULVERIZED RICE HUSK WASTE CATALYTIC COMBUSTION WITH NATURAL ZEOLIT - Hamidi, Nurkholis; Yuliati, Lilis; Purnami, Purnami; Faiz, Naufal Muhammad (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2024)
Rice husk is a type of agricultural waste that generated from rice production activities. The number continues to increase in line with the increasing food needs of the people in Indonesia. This study aims to determine the effect of the addition of natural zeolite as a catalyst and to determine the effect of natural zeolite mass percentage variation in the mixture on rice husk waste catalytic combustion by using the thermo gravimetric analysis method. The results of this study show that there is an effect of adding natural zeolite catalysts with the mass percentage of natural zeolite variations on the combustion characteristics and activation energy of each mixture. Increasing the mass percentage of natural zeolite catalysts can affect the reaction process become faster and minimize the effort required, but it was found that if the amount of natural zeolite catalyst is too much, it only adds to the heating load which causes slower reaction. The mixture of rice husks with 10% natural zeolite catalyst is the most optimal mixture because it has the lowest required activation energy value and the combustion reaction phases are achieved at a lower temperature than 5% and 15% mass percentage variations.